2007
DOI: 10.1177/117693510700300004
|View full text |Cite
|
Sign up to set email alerts
|

Germinal Center B Cell-Like (GCB) and Activated B Cell-Like (ABC) Type of Diffuse Large B Cell Lymphoma (DLBCL): Analysis of Molecular Predictors, Signatures, Cell Cycle State and Patient Survival

Abstract: Aiming to find key genes and events, we analyze a large data set on diffuse large B-cell lymphoma (DLBCL) gene-expression (248 patients, 12196 spots). Applying the loess normalization method on these raw data yields improved survival predictions, in particular for the clinical important group of patients with medium survival time. Furthermore, we identify a simplified prognosis predictor, which stratifies different risk groups similarly well as complex signatures.We identify specific, activated B cell-like (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 29 publications
1
41
0
1
Order By: Relevance
“…The lymphoid-restricted membrane protein (LRMP), is an endoplasmic reticulum-associated protein. We found higher mRNA levels of LRMP in the GCB- compared to the non-GCB-subtype of DLBCL, which demonstrated that it predicted and supported the aggressive behavior of the non-GCB subtype of DLBCL [23, 25]. In this study, we discovered that NONHSAG026900 was clustered with these three protein-coding genes into one functional module for cell cycle regulation by gene co-expression network analysis.…”
Section: Discussionsupporting
confidence: 57%
“…The lymphoid-restricted membrane protein (LRMP), is an endoplasmic reticulum-associated protein. We found higher mRNA levels of LRMP in the GCB- compared to the non-GCB-subtype of DLBCL, which demonstrated that it predicted and supported the aggressive behavior of the non-GCB subtype of DLBCL [23, 25]. In this study, we discovered that NONHSAG026900 was clustered with these three protein-coding genes into one functional module for cell cycle regulation by gene co-expression network analysis.…”
Section: Discussionsupporting
confidence: 57%
“…SH3BP5 has been included in a signature gene set for ABC DLBCL [18,28], and it has been shown to inhibit the autophosphorylation and transphosphorylation activities of BTK in normal B cells [26,29]. A selective BTK inhibitor, ibrutinib, has been shown to be effective in treating several types of B-cell lymphomas, such as chronic lymphocytic leukemia, mantle cell lymphoma, and ABC DLBCL [30].…”
Section: Discussionmentioning
confidence: 99%
“…1). For COO segmentation, multiple predictors have been described in the literature (4,13,19). By combining unique predictors from these studies, a list of 51 distinct genes was obtained (Fig.…”
Section: Definition Of Nanostring and Rt-pcr Gene Lists For Dlbcl Segmentioning
confidence: 99%